Undergraduates Perception Towards The Use of Google Classroom for Learning - Aderele, Shadrack Omotayo; Sanni, Tunde Abdulrahman (Indonesian Journal of Teaching in Science, 2022)
Google Classroom allows teachers to spend more time with their students and less time on the paperwork, and it is now even better. This study assessed the Undergraduates’ Perceived Ease of Use and perceived usefulness of Google Classroom for Learning and the influence of gender on their perception. This research was a descriptive research method of the survey type. The population of this study was all undergraduates in Kwara state. Students were randomly selected from each of the faculties listed to bring the total number of samples to 400. Percentage, mean, and t-test were used for the analysis. The findings established that Undergraduates have a positive perception of the ease of use of Google Classroom for learning with a grand mean score of 3.50; Undergraduates have a positive perception of the usefulness of Google Classroom for learning with a grand mean score of 3.39; There was no significant difference between male and female Undergraduate Students Perceived the Ease of Use of Google Classroom for Learning and There was no significant difference between male and female Undergraduate Students’ Perceived Usefulness of Google Classroom for Learning. The study concluded that undergraduates have a positive perception of the ease of use and usefulness of Google Classroom for learning. This implies that if Google Classroom is adopted in our schools, there will be a tremendous improvement in the academic performance of undergraduates irrespective of their gender and specializations. It was however recommended that the educational authorities and the school system should encourage the use of Google Classroom for learning.